THE ROLE OF THE REHABILITATION CENTER OF THE MINISTRY OF DEFENSE OF THE REPUBLIC OF INDONESIA IN ENHANCING THE QUALITY OF LIFE OF DISABLED SOLDIERS OF THE INDONESIAN NATIONAL ARMED FORCES THROUGH THE UTILIZATION OF ARTIFICIAL INTELLIGENCE - Syahrial, Syahrial (Ridwan Institute, 2024)
The Indonesian National Armed Forces (TNI) are frequently exposed to the risk of physical and mental injuries that may result in disability. The integration of artificial intelligence (AI) into integrated rehabilitation programs has the potential to expedite the recovery process, enhance diagnostic precision, and facilitate more tailored and efficacious care. This study aims to examine the role of Integrated Rehabilitation at the Rehabilitation Center of the Ministry of Defense of the Republic of Indonesia in improving the quality of life for Indonesian national army soldiers with disabilities. The research employs a normative juridical research method to systematically investigate the legal framework underpinning rehabilitation programs for soldiers and explores the potential integration of AI into these processes. The results show that the integrated rehabilitation services at Pusrehab Kemhan can improve the operational efficiency of the rehabilitation centre. The incorporation of AI in rehabilitation processes serves a crucial purpose in the context of improving the effectiveness of rehabilitation services for people with disabilities, especially for TNI soldiers. Despite challenges related to patient data privacy and security, the potential of AI is enormous.